Effect of Expectation on Pain Processing: A Psychophysics and Functional MRI Analysis - Henderson, Luke A.; Di Pietro, Flavia; Youssef, Andrew M.; Lee, Sinjeong; Tam, Shirley; Akhter, R.; Mills, Emily P.; Murray, Greg M.; Peck, Chris C.; Macey, Paul M. (Frontiers in Neuroscience, 2020)
Pain is a complex phenomenon that is highly modifiable by expectation. Whilst the intensity of incoming noxious information plays a key role in the intensity of perceived pain, this intensity can be profoundly shaped by an individual’s expectations. Whilst modern brain imaging investigations have begun to detail the brain regions responsible for placebo and nocebo related changes in pain, less is known about the neural basis of stimulus-expectancy changes in pain processing. In this functional magnetic resonance imaging study, we administered two separate protocols of the same noxious thermal stimuli to twenty-four healthy subjects. However, different expectations were elicited by different explanations to subjects prior to each protocol. During one protocol, pain intensities were matched to expectation and in the other protocol they were not. Pain intensity was measured continuously via a manually operated computerized visual analogue scale. When individuals expected the stimulus intensity to remain constant, but in reality it was surreptitiously increased or decreased, pain intensity ratings were significantly lower than when expectation and pain intensities were matched. When the stimulus intensities did not match expectations, various areas in the brain such as the amygdala, anterior cingulate cortex, dorsolateral prefrontal cortex and the midbrain periaqueductal gray matter displayed significantly different patterns of activity compared to instances when stimulus intensity and pain expectations were matched. These results show that stimulus-expectancy manipulation of pain intensity alters activity in both higher brain and brainstem centres which are known to modulate pain under various conditions.